Creativity in ‘Umran sciences: expopising some aspects of Ibn Khaldun's creative thinking - Machouche, Salah (2014)
Ibn Khaldun is known for his substantial and various contributions to human knowledge. He strongly demonstrated his high thinking abilities in fields of history, economy, education and civilizational studies. Researchers provide different explanation to his achievements as their worldviews, intellectual background, personal objectives and ideological affiliations differ. Yet, some of the researchers did not try to explain Ibn Khakdun’s creativity but to reduce its credibility by claiming its foreign origin. To show the flaws of this later claim, this research exposes Ibn Khaldun’s creativity and it highlights its originality through providing illustration showing its overall aspects and forms within its Islamic context. The research relies on textual analysis of the Muqaddimah and critique of main views of the contemporary researchers in the filed.